Mitochondrial fusion mediated by fusion promotion and fission inhibition directs adult mouse heart function toward a different direction. Issue 1 (26th November 2019) - Qin, Yuan; Li, Anqi; Liu, Bilin; Jiang, Wenting; Gao, Meng; Tian, Xiangang; Gong, Guohua
Abstract: Mitochondrial fusion and fission are essential for heart function. Abrogating mitochondrial dynamism leads to cardiomyopathy. Excessive mitochondrial fragmentation is involved in most heart diseases, thus enhancing mitochondrial fusion will be a potential therapeutic strategy. To understand the effects of promoting mitochondrial fusion in adult cardiac, we investigated mice hearts, and cultured murine embryonic fibroblasts (MEFs), in which mitofusin 2 (Mfn2) overexpressed or dynamin‐related protein 1 (Drp1) was abrogated concomitantly forcing mitochondrial fusion. Parallel studies revealed that fission‐defective Drp1 knockout hearts and MEFs evoked stronger mitochondrial enlargement, enhanced mitophagy with mitochondrial volume decrease and increased mitochondrial calcium uptake, superoxide production, and permeability transition pore opening, contributed to cardiomyocyte apoptosis and dilated cardiomyopathy. Mfn2 overexpression in the adult heart is comparable with the control except for slight mitochondrial enlargement and mitochondrial volume increase, but without mitophagy induction. Moreover, Mfn2 overexpression increases mitochondrial biogenesis and fusion could protect against mitochondrial fragmentation and Drp1 deletion evoking mitophagy in MEFs. Our findings indicate that mitochondrial fusion provoked by fusion promotion and fission inhibition direct the different fate of heart, Mfn2 upregulation other than Drp1 downregulation well maintains heart mitochondrial function is a more safe strategy for correcting excessive mitochondrial fragmentation in hearts.